(untitled) (Edinburgh, 2002)
Still unique in the field, this text combines color photographs and full-color artwork in one convenient resource. The dissections are amazingly clear, almost 3-D in appearance, and color-coded artwork next to each photo makes anatomy easy to interpret and identify.
Keywords: Human anatomy,Anatomy